Firm Resources and Sustained Competitive Advantage - Barney, Jay (Journal of Management, 1991)
Understanding sources of sustained competitive advantage has become a major area of research in strategic management. Building on the assumptions that strategic resources are heterogeneously distributed acrossfirms and that these differences are stable over time, this article examines the link betweenfirm resources and sustained competitive advantage. Four empirical indicators of the potential of firm resources to generate sustained competitive advantage-value, rareness, imitability, and substitutability-are discussed. The model is applied by analyzing the potential of severalfirm resourcesfor generating sustained competitive advantages. The article concludes by examining implications of this firm resource model of sustained competitive advantage for other business disciplines.